Observer dependence of entanglement in nonrelativistic quantum mechanics - Zambianco, Matheus H. [UNESP]; Landulfo, André G.S.; Matsas, George E.A. [UNESP] (American Physical Society (APS), 2019)
It was recently shown that, in general, the von Neumann spin entropy of fermionic particles is not invariant under Lorentz boosts. We show that an analogous result can be recovered (at the lowest order of v2/c2) using plain nonrelativistic quantum mechanics provided one uses that energy weighs: E=mc2. This should (i) help to moderate the skepticism on the observer dependence of the spin entropy of fermionic particles, (ii) emphasize the soft relativistic nature of this result, and (iii) show that this is a particular case of a more general class of systems, since our calculation only assumes a nonrelativistic particle endowed with an internal degree of freedom.